Productivity and economic value added drive swine production sustainability - Rita Therezinha Rolim Pietramale; Carolina Obregão da Rosa; Daiane Pereira de Souza; Gabriela Vilela dos Santos Mantovani; Fabiana Ribeiro Caldara; Clandio Favarini Ruviaro (Discover Sustainability)
Abstract Context Swine production plays a vital role in economic development; however, balancing productivity with environmental and financial sustainability remains a challenge. Objective This study introduces an integrated approach combining Life Cycle Assessment (LCA) and Economic Value Added (EVA) to assess eco-efficiency in Brazilian piglet production, a stage often underrepresented in sustainability research. Methods A Life Cycle Assessment was conducted to quantify environmental impacts, and EVA was used to evaluate financial performance. The analysis relied on data from 2016 to 2021, including greenhouse gas emissions, land use, and economic returns. Results and conclusions Results indicate that improvements in sow productivity led to lower GHG emissions per kilogram of piglet and that eco-efficiency varied with market conditions. In 2021, increased productivity and favorable prices resulted in positive EVA and a 7.8% land use reduction. Significance This study underscores the value of integrating environmental and economic assessments to support decision-making in swine systems. By applying the LCA–EVA framework to piglet production, this research provides insights to enhance the sustainability of pork value chains.